Quality of current ischaemic stroke care practices in the Cape Metro Health District, South Africa - Mandizvidza, Vimbai (Department of Public Health and Family Medicine, 2018)
The aim of this study was to assess the acute and post-acute services for ischaemic stroke patients in the Cape Metro Health District in relation to the South African ischaemic stroke guideline. Part A: Protocol - The protocol outlines the purpose of the study and highlights the importance of conducting this study by analysing the literature on stroke care in both high and low and middle-income countries. The literature also highlights the gaps in stroke care in South Africa which justify the need for this study. The protocol also outlines the methods of data collection and analysis as well as the ethical considerations. Part B: Literature Review - This expands on the literature on the different components of both acute and post-acute stroke care in both high and low and middle-income countries. It also elaborates on stroke in South Africa and why it is important to conduct this study. Part C: South African Medical Journal manuscript - The manuscript summarises the whole study and includes the literature on stroke care, justification of the study and how the data was collected and analysed. The manuscript also includes the results obtained and sections on the discussion and conclusions.